VARIASI MORFOLOGI POLYGONUM SPP DAN KEKERABATAN JENIS - Sihombing, Pariama
ABSTRAK: Morphological variation of Polygonum Spp and the species relationship Observation had been done on the morphology and anatomy of seven taxa of Polygonum L. (Polygonaceae) to find out the phenetic relationship among the taxa. The taxa observed were : Polygonum hydropiper L., Polygonum barbatum L., Polygonum perfoliatum L., Polygonum longisetum De Br., Polygonum chinense L., Polygonum minus ssp micranthum Dans., and Polygonum minus ssp depressum Dans. For morphological observation, the plant\'s organ were observed qualitatively and quantitatively on it\'s stem, ocrea, leaf petiol, leaf and flower. For anatomical observation those were trachea and tracheid cells of the root and stem observed using maceration method, and for stem cross section, parafin method was used. From the morphological and anatomical observation, 60 characters were studied, which number of characters were the minimum requirements for the cluster analysis method. In the observation of the morphology of those organs mentioned above, it was found that there were some varieties. The variations were shown through the ocrea which were the specific character of the genus of Polygonum, it could be leaf-like or tube-like. Nevertheless, for stem, leaf petiol and lower surface of the leaves it could be spiny or hairy. The inflorescence of the seven taxa observed could be a spike or a panicle. Using cluster analysis with 60 characters based onthe similarities, a dendrogram or phenogram could be constructed to show the relationship between one taxon to the others. The result of the cluster analysis showed two groups of taxa. Group I, consists of five taxa, namely . P. minus ssp rr:icranthum Dans . , P. minus ssp depressum Dans . , P. Longisetum De Br., P.hydropiper L,, and P.barbatwn L., and group II, consists of two taxa, namely : P.chinense L., and P.perfoliatwn L. The result of the observation showed that P.minus ssp micrantum Dans. closely related to P.minu ssp depressum Dans. which was connected to phenon line 90 ( having similarity of 90 %). Both taxa are related to P. hydropiper, P.barbatum and P.Longisetum on phenon line 70 %. The five taxa from group I which were connected to phenon line 69 with P.chinense, whereas the relationship between taxa from group I and taxa P.chinense and P.perfoliatwn is expressed by phenon line 50. This is shown by the difference of P. perfol iatwn compared to other taxa, the difference are found in ocrea, stem, leaf petiole and lower surface of the leaves. P.chinense is found between P.perfoliatum and the other taxa of Polygonwn ; this can be shown by the shave of the leaves of P.perfoliatwn, but the tube form of it\'s ocrea is similar to that of the other taxa of PoLygonum. P. chinense has an auricle on the base of it\'s leaf petiol and this is a specific character, whereas other Polygonum spp does not have this characteristic.